Discovery and optimization of a synthetic small protein domain targeting antibodies - Dias, Ana Margarida Gonçalves Carvalho; Matos, Manuel João Brandão; Soares, Cátia; Natal, Carolina; Pina, Ana Sofia; Roque, Ana Cecília Afonso (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAntibodies and their derivatives constitute a crucial class of molecules in modern biotechnology and therapeutic development. Consequently, identifying chemically robust affinity ligands capable of specifically recognizing antibodies remains an important challenge.MethodsIn this study, an in-house phage display library based on the WW domain scaffold (WWp5_4) was utilized to identify binders against polyclonal human IgG. A lead ligand from clone E6 was selected. To enhance the developability of WW ligands derived from this library, we rationally minimized structural liabilities within the scaffold framework to improve chemical stability and solubility, generating two mutant variants. Furthermore, a head-to-tail dimeric version of the E6 mutant sequence was designed.ResultsThe lead ligand E6 exhibited a dissociation constant of 133 nM. The mutant variants demonstrated a fivefold increase in expression yield compared to the native sequence. Additionally, the dimeric construct showed improved solubility and an estimated dissociation constant of 62 nM toward human IgG.ConclusionsThis study underscores the potential of small folded protein domains, such as WW domains, as versatile affinity ligands for antibodies and other molecular targets, thereby broadening their applicability in biotechnology and bioengineering.